Speech Outcomes of a National Cohort of Children with Orofacial Cleft at 5 and 10 Years of age. (November 2022) - Morrison, Maeve M.; Mason, Nicola T.; Forde, Bryony L.; Stone, Peter R.; Fowler, Peter V.; Thompson, John M. D.
Objective: To assess speech outcomes at five and ten years of age in a nationwide study of children with orofacial cleft. Design: Prospective study. Participants: Children born with orofacial cleft and having primary surgery in New Zealand. Speech samples were available for 151 five-year-old, and 163 ten-year-old children. Main outcome measures: Intelligibility, Acceptability, Velopharyngeal function, Hypernasality, Hyponasality, severity of airflow evaluated by perceptual speech assessment (using the standardised Rhinocleft assessment), and overall assessment of requirement for clinical intervention. Results: A large proportion of five-year-old children had speech that was considered to be not completely intelligible, was not acceptable, and had inadequate velopharyngeal function. The noted deficiencies led to a clinical judgement that further speech and/or surgical intervention was required in 85% with cleft lip and palate, 65% with cleft palate and 26% with cleft lip. The proportion of children with poor speech outcomes in the ten-year-old children was lower, though of clinical importance, further intervention required for 25% with CLP, 15% with CP and 3% with CL. The number of sound production errors in both age groups followed the same pattern with fewest in those with CL and most in those with CLP. Conclusions: A significant proportion of children with orofacial cleft were found to have poor speech outcomes requiring further treatment. The outcomes are poor compared to centres reported in the UK and Scandinavia. New Zealand requires a review of the current services for individuals born with cleft to improve speech outcomes and interdisciplinary care.